Influence of prenatal class to the practice of P4K (Birth Planning and Prevention of Birth Complication) - Robitha Faiza; Hari Basuki Notobroto; Bambang Trijanto; Oedojo Soedirham; Ah. Yusuf; Kusuma Halim (Universitas Airlangga, 2016)
Objective: This study aimed to analyze the influence of prenatal class to the practice of P4K (Birth Planning And Prevention Of Birth Complication).Materials and Methods: This study applied analytical survey with cross sectional approach. The number of samples taken was as many as 30 mothers, using simple random sampling. Analysis of data was carried out using ordinal wilcoxon sign rank test. Datas were obtained from interviews and questionnaire.Result: The influence of prenatal class to practice of P4K (Birth Planning and Prevention of Birth Complication) (p = 0,0000). Conclusion: Prental class can influence to practic of P4K.